2009
DOI: 10.1063/1.3263683
|View full text |Cite
|
Sign up to set email alerts
|

Importance of centrifugal effects for the internal kink mode stability in toroidally rotating tokamak plasmas

Abstract: Analytical theory and two different magnetohydrodynamical stability codes are used in a study of the effects of toroidal plasma rotation on the stability of the ideal, internal kink mode in tokamaks. The focus of the paper is on the role that the centrifugal effects on the plasma equilibrium play for the stability of this mode, and results from one code where centrifugal effects are self-consistently included ͑CASTOR-FLOW͒ ͓E. Strumberger et al., Nucl. Fusion 45, 1156 ͑2005͔͒ are compared with the results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…The dispersion relation for the ideal MHD instability, whose effects of toroidal rotation are almost exclusively confined to the inertial enhancement, yields complex frequencies and thus modified growth rates [27]. These physical phenomena have been verified in a detailed study of the internal kink mode [8], where analytic work has carefully identified that centrifugal and coriolis effects effects are physical, and where benchmarking against a full MHD codes in which toroidal rotation was self consistently included in the equilibrium and the linearly perturbed MHD equations.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The dispersion relation for the ideal MHD instability, whose effects of toroidal rotation are almost exclusively confined to the inertial enhancement, yields complex frequencies and thus modified growth rates [27]. These physical phenomena have been verified in a detailed study of the internal kink mode [8], where analytic work has carefully identified that centrifugal and coriolis effects effects are physical, and where benchmarking against a full MHD codes in which toroidal rotation was self consistently included in the equilibrium and the linearly perturbed MHD equations.…”
Section: Discussionmentioning
confidence: 74%
“…In Ref. [8] it was shown that continuum modes oscillating at the Brunt-Väisälä [9] frequency directly impacts the stabilily threshold of the internal kink mode, and that inconsistent treatment of the effect of toroidal rotation on the continuum mode would lead to erroneous results. The mode oscillating at the Brunt-Väisälä frequency is in fact a finite n zonal mode, which arises as one of two roots [10] from a dispersion relation that also defines the geodesic acoustic mode.…”
Section: Introductionmentioning
confidence: 99%
“…Typically in a tokamak 2 < 0 so that S f is stabilizing. A potential energy term proportional to ρ 2 was found in [17] and [11,51] in relation to ballooning modes and the internal kink mode, respectively.…”
Section: The Flutter Term S Fmentioning
confidence: 99%
“…Whilst treating the rotation only in the stability analysis can be a valid approximation at very sub-Alfvénic rotation velocities, it can also lead to significantly misleading, or even erroneous results [23,24]. The stability of over 6000 equilibria with different pressures, toroidal rotation velocities and profiles has been tested.…”
Section: Equilibriamentioning
confidence: 99%